Multiparty Evolutionary Game Strategy for Green Technology Innovation Under Market Orientation and Pandemics - Min Gong; Min Gong; Aiming Dai (Frontiers Media S.A., 2022)
Building a market-oriented green technology innovation system is important for China's green development. In this system, the government, enterprises, and consumers promote green innovation. Given this backdrop, this study constructs an evolutionary game model that combines the government, enterprises and consumers to analyse their evolution trend of strategy by simulating theoretical analyses. It is found that government subsidies for enterprises and consumers, benefits of enterprises speculation, and green consumption costs affect the enterprise decisions of green innovation. These factors significantly affect the enterprises' decision-making of green technology innovation. It is also observed that the market mechanism motivates enterprises' green technology innovation under pandemics. It is suggested that adopting more green consumption subsidy policies, improving the supervision mechanism and formulating more incentive policies from other aspects will be useful policy implications.